Pengaruh Bokashi Dan POC Bintang Kuda Laut Terhadap Petumbuhan Dan Hasil Terung (Solanum melongena L.) - Fadli, Mohamad; Taufik Y., M. Bayu (Jurnal Magrobis, 2015)
The purpose of research was to know the effect of Bokashi and POC Bintang Kuda Laut to the growth and yield of eggplant.The research was conducted on April to July 2013 at Loa Ipuh, sub distric of Tenggarong. The research was arranged in Randomized Complete Block Design (RCBD) with 4x4 analysis factorial and three replications. The first factor was of Bokashi (B) consisted of four levels i,e ; b0 (control), b1 (5 t Bokashi fertilizer ha-1),b2 (7,5 t Bokashi fertilizer ha-1) and b3 (10 t Bokashi fertilizer ha-1).The second factor was POC Bintang Kuda Laut (P) consisted of four levels i.e p0 (control), p1 (0.001 L-1 condensation), p2 (0.002 L-1 condensation) and p3 (0.003 L-1 condensation).The result of research showed that Bokashi were significantly affected to the all parameters. The highest weight of yield per plant of was obtained at Bokashi b3 (10 t pupuk Bokashi ha-1) with average 4.37 kg to compared of control was average 3.40 kg.The effect of POC Bintang Kuda Laut showed were significantly affected to the all parameters. The highest weight of yield per plant of was obtained at p3 (0.003 L-1 condensation) with average 4.23 kg to compared of control was average 3.41 kg. No Interaction between Bokashi and POC Bintang Kuda to the all parameters.Keyword : bokashi, POC bintang kuda laut, eggplant